Development of Tourism Village (Curug Payung) and Religious Tourism (Gunung Sanggar) in the Village Gunungmanik - Arie Susetio utami; Muhamad Nana Trisolvena; johan; Tri Budi Prasetyo (Ann Publisher, 2023)
Gunungmanik Village has a lot of potential natural resources. The air is always cool andfresh. The livelihood of the residents of Gunungmanik Village is vegetable farmers. Local customsand wisdom still exist in Gunungmanik Village. In addition, there is religious tourism inGunungmanik Village, namely the tomb of Sheikh Sanggar Waringin in Gunungsanggar, in JatirasaHamlet located on the hillside. Curug Payung in Ciraharja Hamlet is one of the natural attractions inGunungmanik Village, which stores the beauty of a very amazing natural panorama with cool air.Community service activities have been carried out in Curug Payung to introduce nature andreligious tourism to the general public. This will make Gunungmanik village richer with prehistoricplaces and interesting natural attractions. The purpose of community service is to fulfill the duties inthe 2022 KKM program of the University of Muhammadiyah Cirebon Mengabdi. Activities arecarried out through counseling, observation, training, and interviews. Community service reports inthe form of observations and analysis result that Gunungmanik deserves to be a tourist village inKuningan. Its beautiful environment is also an attraction for the village. The results of the externalenvironment analysis show that the condition of other tourist villages in the surrounding location isstill small and government support for this tourist village is very good.